2021
DOI: 10.3390/vaccines9060586
|View full text |Cite
|
Sign up to set email alerts
|

Scale-Up Production of Type O and A Foot-and-Mouth Disease Bivalent Vaccine and Its Protective Efficacy in Pigs

Abstract: South Korea has experienced FMD outbreaks almost every year since 2014. Therefore, a novel local vaccine that can cover various topotypes of viruses is required. Two virus strains, O/Boeun/SKR/2017 and A/Yeoncheon/SKR/2017, were cultured up to the pilot scale based on the optimized conditions set up on the flask scale. FMDV particles (146S) of 2 µg/mL or more were obtained from the virus culture supernatant using a 100 L bioreactor. The viruses were fully inactivated using binary ethylenimine within 16 h throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Currently, three topotypes of serotype O viruses (SEA, Cathay and ME-SA) are circulating in the region ( Table 1 ), although historically SEA countries were home to SEA and Cathay topotype viruses. The O/ME-SA/PanAsia strain spread to SEA countries in early 2000, causing devastating economic consequences [ 12 , 13 , 14 ]. One decade later, in early 2010, another ME-SA strain (O/Ind-2001) from the Indian subcontinent spread to these countries [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Currently, three topotypes of serotype O viruses (SEA, Cathay and ME-SA) are circulating in the region ( Table 1 ), although historically SEA countries were home to SEA and Cathay topotype viruses. The O/ME-SA/PanAsia strain spread to SEA countries in early 2000, causing devastating economic consequences [ 12 , 13 , 14 ]. One decade later, in early 2010, another ME-SA strain (O/Ind-2001) from the Indian subcontinent spread to these countries [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it appears that the existing v / s are broadly cross-reactive and can provide protection against the circulating topotypes, except Cathay viruses, as demonstrated previously using O 1 /Campos v / s [ 24 , 25 ]. Several studies, mainly from South Korea, have reported the suitability of new putative strains for use in both pigs and cattle in their control programs [ 13 , 14 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although vaccination is the key to control serotype O FMD, the available vaccines are not able to provide enough cross-protection as outbreaks still occurred despite repeated vaccinations ( Mahapatra et al, 2017 ; Lee et al, 2020 ; Park et al, 2021 ). The vaccines used showed a good match with the O/SEA and O/ME-SA viruses, whereas none of the recently circulating O/Cathay viruses were protected by any of the vaccine strains, including the existing O/Cathay vaccine, indicating an antigenic drift and the urgency to develop new vaccine strains ( Upadhyaya et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%